Subjective experiences of older adults in poverty in urban China and the role of social policy. Issue 1 (2nd January 2018) - Chen, Yan-Yan; Walker, Robert; Hong, Liu
Abstract: This study establishes an evidence base regarding the experiences of older adults living in poverty in Beijing. Given the factors that shape the lives of low-income older adults, the findings are relevant for many middle- and low-income countries. Based on a series of in-depth interviews conducted with government officials and low-income older adults in Beijing, the study finds that poverty manifests as cumulative stress arising from four sources: financial strain, poor health, care burden and poverty-related shame. This stress is attributable to the co-existence of individual and structural factors that reflect the framing of anti-poverty policies in China.